(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Local scour around the pier is one of the main reasons for bridge failures in the world. Many studies have been conducted to assess the hydraulic performance of different types of countermeasures designed against scouring. Generally, the countermeasures can be classified into two groups: flow-altering and bed-armoring techniques. Collar is the most commonly used countermeasure to change the flow around the pier, hence reducing local scour depth. This paper briefly reviews the most up-to-date studies regarding using the collar method as a protective technique for the pier. The reviewed studies indicated that the amount of scour reduction around the collar-protected pier is based on the size, shape, and position of the collar. The rectangular collar outperforms better than circular, trapezoidal, and triangular shapes under the same conditions. Additionally, combination the collar with other types of countermeasures can enhance the scour reduction process.